OZONE THERAPY IN POSTOPERATIVE PLASTIC SURGERY INJURIES - Carla Soares Silva, Ediana; Rodrigues Sousa, Enos (Health and Society, 2023)
The current article deals with ozone therapy in the postoperative needs of plastic surgery, with the following objectives: to explain the use of ozone therapy but before plastic surgery surgeries, to point out the involvement of the lesions and to detail the applications of ozone therapy. As for the methods, bibliographic research was used, carried out in a judicious way, taking into account the subject addressed, with material of great accessibility to the public. About the discussion: the attempt is that the technique is presented and the attempt to treat the answers, a more satisfactory result. And as a conclusion: it is understood that azonium therapy is effective as a treatment.